Moenkhausia andrica (Characiformes: Characidae): a new species from the rio Tapajós basin, Brazil, with minute fin hooklets in females - Reia, Lais [UNESP]; Oliveira, Claudio [UNESP]; Benine, Ricardo C. [UNESP] (Wiley, 2021)
In this study, a new species of Moenkhausia is described from the upper rio Juruena, rio Tapajós basin, Brazil. It is distinguished from all congeners by the presence of minute bony hooks in all fins of both mature females and males and combination of a prepelvic region flattened, dorsal portion of the humeral blotch extending two scales horizontally and vertically, lateral line with 28–32 scales, five scale series above and below lateral line; circumpeduncular scales 13–14, anal-fin rays 16–19 and dorsal portion of eyes blue in live specimens. The new species is also supported by high divergence in the mitochondrial gene cytochrome c oxidase subunit I (COI). The presence of minute fin bony hooks in both females and males, population variations and late development of the lateral line in Moenkhausia andrica are discussed.
Keywords: freshwater fishes; Juruena; Moenkhausia oligolepis/Moenkhausia sanctaefilomenae complex; secondary sexual character